2011
DOI: 10.1007/s10120-011-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of demographics and surgical practice for patients with gastric cancer in two centers: in Poland versus Germany

Abstract: BackgroundAlthough studies comparing the surgical treatment of gastric carcinoma in Japan and Western industrialized countries have revealed differing survival rates, no studies to date have been performed comparing Western and Eastern Europe. This study aimed to compare demographics and surgical practice as well as the related prognostic impact on gastric cancer patients treated in Poland and Germany.MethodsThis retrospective study included gastric cancer patients treated between 1999 and 2004 by surgical dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…Geographic variation in survival was clinically meaningful; however, the differences were not statistically significant. Intraprovincial regional variation in surgical practice patterns and outcomes for patients with stages i-iii resected gc in our study supports other research in gc care in the United States 15,16 , the Netherlands 9 , and other low-incidence countries 17,18 . A comparative European study of patients with resected gc highlighted variation in operative mortality and rates of positive resection margins for England, Denmark, Sweden, and the Netherlands 19 .…”
Section: Discussionsupporting
confidence: 87%
“…Geographic variation in survival was clinically meaningful; however, the differences were not statistically significant. Intraprovincial regional variation in surgical practice patterns and outcomes for patients with stages i-iii resected gc in our study supports other research in gc care in the United States 15,16 , the Netherlands 9 , and other low-incidence countries 17,18 . A comparative European study of patients with resected gc highlighted variation in operative mortality and rates of positive resection margins for England, Denmark, Sweden, and the Netherlands 19 .…”
Section: Discussionsupporting
confidence: 87%
“…The goal of treating chondrosarcomas is their radical resection [ 6 , 7 ]. It is important for patients with these tumors to be treated in experienced medical centers, as only interdisciplinary management may result in achieving the best outcomes [ 8 – 10 ]. Frequently, non-standard management is required as well as the participation of both oncological and thoracic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…As there are no clear standards on the subject, the management of desmoid tumors should always be tailored to individual patients, and the employed treatment should consider the patient's quality of life. Apart from physical examination and imaging examinations, intraoperative assessment of the tumor is the most important factor for deciding whether the tumor can be resected [ 8 – 10 ]. In the present case, radical surgery alone was considered to be the most appropriate treatment option for our patient.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature data, these two types of neoplasms require different operative strategies in order to achieve a radical resection. In the case of adenocarcinoma of the cardia, this requires gastrectomy with resection of the distal part of the esophagus and thoracic anastomosis [ 8 ]. In view of the diagnosis of squamous carcinoma of the cardia, a decision was made to perform additional resection of the thoracic segment of the esophagus with cervical anastomosis due to the increased risk of skip metastases associated with this type of tumor and in order to perform two-field lymphadenectomy [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most authors agree that surgical treatment of esophageal cancer should be performed in centers that employ surgeons with excellent operative technique and sufficient experience with regard to the proper selection of patients for the procedure [ 1 , 9 ]. The authors of this report work at a clinic which has over 40 years of experience with treating esophageal cancer [ 8 ]. In the present case, preoperative endoscopy and computed tomography indicated that it was feasible to perform esophageal resection using the Akiyama method.…”
Section: Discussionmentioning
confidence: 99%